2016
DOI: 10.1002/rem.21481
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Nano Zerovalent Iron in In Situ Chemical Reduction: Challenges and Improvements

Abstract: Nano zerovalent iron (nZVI) is a promising remediation technology utilizing in situ chemical reduction (ISCR) to clean up contaminated groundwater at hazardous waste sites. The small particle size and large surface area of nZVI result in high reactivity and rapid destruction of contaminants. Over the past 20 years, a great deal of research has advanced the nZVI technology from bench‐scale tests to field‐scale applications. However, to date, the overall number of well‐characterized nZVI field deployments is sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 41 publications
1
58
0
1
Order By: Relevance
“…This was benefited from MWCNTs as a carbon‐based material was capable of CT adsorption, as shown in Figure S2, CT could be adsorbed rapidly by MWCNTs from aqueous phase to catalyst surface, and MWCNTs without loss the capacity of CT adsorption in five consecutive cycles. Moreover, the pH variations of dechloriantion process were also monitored, Figure shown that 2N 4 F@MWCNTs had a lower pH while with satisfactory reusability, which meant 2N 4 F@MWCNTs could evolve more H 2 under lower pH solution and has an excellent dechlorination performance …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This was benefited from MWCNTs as a carbon‐based material was capable of CT adsorption, as shown in Figure S2, CT could be adsorbed rapidly by MWCNTs from aqueous phase to catalyst surface, and MWCNTs without loss the capacity of CT adsorption in five consecutive cycles. Moreover, the pH variations of dechloriantion process were also monitored, Figure shown that 2N 4 F@MWCNTs had a lower pH while with satisfactory reusability, which meant 2N 4 F@MWCNTs could evolve more H 2 under lower pH solution and has an excellent dechlorination performance …”
Section: Resultsmentioning
confidence: 95%
“…It can be learned from Table that the 2N 4 F@MWCNTs possessed lowest concentration of dissolved cations but highest loss rate after five times reactions compared with nZVI and N 4 F. Lowest dissolution signified a slight negative environment impacts, and the relatively high loss rate may attribute to severe corrosion on the bimetallic surface due to the large reaction specific surface area. Besides, more H 2 evolution by 2N 4 F@MWCNTs means less Fe 0 was directly involved in the process of CT dechlorination …”
Section: Resultsmentioning
confidence: 99%
“…As noted above, however, this does not necessarily imply that these reactions occur (only) by electron transfer mechanisms, because various atom-transfer reactions can also contribute to redox reactions. In previous work, 32 we have tried to address this issue by using the more general term "reducing equivalents", but that is not continued in this work for simplicity and consistency with the majority of other work on this topic. Also, for modied ZVI, and in particular suldated ZVI, electrons from iron sulde are not considered here because the dechlorination of organohalides (e.g., TCE) by FeS is typically much slower than dechlorination by suldated ZVI.…”
Section: Determination Of Electron Efficiency (3 E )mentioning
confidence: 99%
“…These objectives were addressed using a series of laboratory experiments conducted in a thin flow cell and using the reaction of sodium borohydride (NaBH 4 ) and water to exsolve H 2 as a novel method to investigate the effects of internal drainage. In addition to providing a useful laboratory technique, the exsolution of H 2 is of particular interest because of its importance to the remediation of chlorinated organics by the injection of nanoscale zero‐valent iron (nZVI) (Fan et al, 2016; O’Carroll et al, 2013; Qin et al, 2018; Johnson et al, 2013). The production of H 2 by the reaction of water with both nZVI and NaBH 4 , which has been applied in excess for nZVI synthesis, can result in the alteration of flow paths away from target treatment areas (Johnson et al, 2013) by blocking pores, as has also been reported for zero‐valent iron used in permeable reactive barriers (Ruhl and Jekel, 2014; Jeen et al, 2012).…”
mentioning
confidence: 99%